Sexuality and Gender in the current BNCC: possibilities and limits - Solange Aparecida de Souza Monteiro; Paulo Rennes Marçal Ribeiro (Universidade Federal do Oeste da Bahia, 2020)
The debate on issues involving Gender and Sexuality has been gaining strength and attention in different spaces and social circles. These questions are combined with the struggle for human rights, democracy and conscious education. It is on this last aspect that the present article aims to discuss: the expansion of feminist movements and the discussions of Gender and Sexuality have provided relevant impacts for education? To answer this question this article analyzes the current normative document on Basic Education, the National Common Curricular Base, conjecturing if there is progress or decline in the treatment of issues involving Gender and Sexuality.